UPAYA HUKUM PENUNTUTAN TINDAK PIDANA PEMBOBOLAN KARTU KREDIT MELALUI INTERNET DI KEJAKSAAN NEGERI DELI SERDANG - Agustian Sinurat; Alpi Sahari (JURNAL DOKTRIN REVIEW, 2023)
The development of science and technology has shown beneficial results for human life, while on the other hand it has also given rise to social ills such as those that have an impact on the emergence of a crime, including carding crimes using computer capabilities to steal personal data from credit card owners. The formulation of the problem is what isthe mode of crime of credit card burglary via the internet in Indonesia, and what are the legal remedies and prosecution of criminal acts of credit card burglary via the internet at the Deli Serdang District Attorney, and what are the obstacles faced by the public prosecutor at the Deli Serdang District Attorney in the criminal credit card theft via the internet. The modus operandi of card fraud via the internet is in the form of discovering the credit card number to pay for ordering goods offered through internet sites, and for this act can be applied using Article 362 of the Criminal Code. Proof can use evidence as contained in Article 184 of the Criminal Procedure Code